가스 파이프라인용 볼 밸브 내부유동의 실험적 연구 - 김철규(Chul-kyu Kim); 이상문(Sang-moon Lee); 장춘만(Choon-man Jang) (한국수소 및 신에너지학회 논문집, 2016)
This paper presents the flow characteristics of a ball valve used for a gas pipeline. Understanding of the internal flow of a ball valve is an important to analyze the physical phenomena of the valve. Present experimental study was performed by IEC 60534-2-3, the international standard for an industrial control valve testing procedure. Pressure measured at upstream and downstream of the valve, flow-rate and gas temperature passing the inside of the gas pipeline were measured with respect to valve opening rates. Throughout the experimental measurement of the ball valve, empirical equation of the pressure drop between the ball valve according to the mass flow rates is successively obtained using a polynomial curve fitting method. In addition, flow coefficient for determining the valve capacity is also analyzed with respect to valve opening rates using the curve fitting method.